Birth month associations with height, head circumference, and limb lengths among peruvian children. Issue 1 (30th January 2014) - Pomeroy, Emma; Wells, Jonathan C.K.; Stanojevic, Sanja; Miranda, J. Jaime; Cole, Tim J.; Stock, Jay T.
ABSTRACT Associations between season of birth and body size, morbidity, and mortality have been widely documented, but it is unclear whether different parts of the body are differentially sensitive, and if such effects persist through childhood. This may be relevant to understanding the relationship between early life environment and body size and proportions. We investigated associations between birth month and anthropometry among rural highland (n = 162) and urban lowland (n = 184) Peruvian children aged 6 months to 8 years. Stature; head‐trunk height; total limb, ulna, tibia, hand, and foot lengths; head circumference; and limb measurements relative to head‐trunk height were converted to internal age‐sex‐specific z scores. Lowland and highland datasets were then analyzed separately for birth month trends using cosinor analysis, as urban conditions likely provide a more consistent environment compared with anticipated seasonal variation in the rural highlands. Among highland children birth month associations were significant most strongly for tibia length, followed by total lower limb length and stature, with a peak among November births. Results were not significant for other measurements or among lowland children. The results suggest a prenatal or early postnatal environmental effect on growth that is more marked in limb lengths than trunk length or head size, and persists across the age range studied. We suggest that the results may reflect seasonal variation in maternal nutrition in the rural highlands, but other hypotheses such as variation in maternal vitamin D levels cannot be excluded. Am J Phys Anthropol 154:115–124, 2014. © 2014 Wiley Periodicals, Inc.